Fatwa and Sociological Awareness: The Role of Halal Fatwa and Its Influence on Consumer’s Purchasing Decisions of Korean Food Products - Eljohani, Mohammed Sayah S.; Zahira, Afrida; Soelistijono, Yati Nurhayati; Jehan, Adam; Mujahidin, Ali (Graduate School of Syarif Hidayatullah State Islamic University Jakarta, 2024)
The increasing popularity of Korean food in Indonesia, driven by global trends and Muslim consumer interest, significantly impacts the non-oil and gas sector's GDP, particularly the food and beverage industry. Halal certification plays a vital role in ensuring that food production complies with Islamic law, enhancing product competitiveness and consumer trust in Indonesia's predominantly Muslim market. This study examines the influence of halal fatwas on purchasing decisions for Korean food, employing a normative legal method and a sociology of law approach through interviews with 20 respondents aged 20-30. The findings reveal that 86% of respondents prioritize halal labels, 63% feel more comfortable consuming halal-certified products, and most are hesitant to try uncertified products. Halal certification emerges as both a legal necessity and a marketing strategy to secure market share. Applying Hans Kelsen's legal certainty theory, the study highlights how clear, consistent halal norms build consumer trust, influencing purchasing behavior and boosting market competitiveness for Korean food products in Indonesia.